Chemical precedent studies probing quantum-mechanical tunneling in hydrogen abstractions facilitated by coenzyme B12 - Doll, Kenneth M., author; Finke, Richard G., advisor; Rappé, Anthony K., committee member; Debruin, Kenneth E., committee member; Ladanyi, Branka M., committee member; Woody, Robert W., committee member (Colorado State University. Libraries, 2003)
Recently, there have been numerous reports regarding the possible involvement of quantum mechanical tunneling in enzyme reactions that involve hydrogen transfer. The first chapter of this dissertation reviews the recent literature in this area, focusing on coenzyme B12 systems. The next three chapters of this dissertation focus on the experimental quantification of an enzyme's involvement in tunneling, which can only be studied by a comparison of the same reaction both inside and outside of the enzyme. The solution thermolysis reaction of coenzyme B12 has been shown to cleanly generate adenosyl radicals that can abstract hydrogen from ethylene glycol, the same reaction that is observed in coenzyme B12-dependent diol dehydratase. We have compared our solution data to the literature enzyme data and to another well studied enzyme, methylmalonyl-CoA mutase. In order to further our knowledge in this system, we have also synthesized 8-methoxyadenosylcobalamin, a methoxy analog of coenzyme B12. This methoxy analog has demonstrated similar abstraction reactivity to coenzyme B12, but with simpler reaction kinetics. A third system was also studied utilizing neopentyl cobalamin. In this system, we were able to monitor the thermolysis and abstraction reactions at lower, enzyme relevant temperatures. These systems have allowed us to conclude that in coenzyme B12 systems, enzymes may exploit quantum mechanical tunneling but have not evolved to enhance it.
Keywords: chemistry; biochemistry; inorganic chemistry